Pengembangan Bahan Ajar Tematik Terpadu Berbasis Model Reciprocal Teaching Untuk Siswa Kelas IV Sekolah Dasar - Dina Dahliana; Pio Anggraini (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2021)
Development of integrated thematic teaching materials based on reciprocal teaching models for grade IV elementary school. Teachers are very involved in developing effective teaching materials for the progress of students in learning. Meanwhile, the existing teaching materials still need improvements because there are several errors such as paragraphs in the reading that are not aligned left-right, capital letters errors. Therefore, to solve this problem, it is necessary to find a solution in the form of developing integrated thematic teaching materials based on the reciprocal teaching model for grade IV elementary school students. This articles aims to produce valid teaching materials. This type of research is development research using the 4-D model (four D models). The model consists of four stages, namely defining (defining), designing (designing), developing (developing), and spreading (deseminating). The results showed that the integrated thematic teaching materials using the reciprocal teaching model obtained the proportion of validity of teaching materials and lesson plans were 87.5% (material) with a very valid category, 75% (language) with a valid category, and 81.8% (design). with a very valid category. While the proportion of RPP is 90% with very valid category.